2012
DOI: 10.3989/gya.010112
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherols and phytosterols in sunflower seeds for the human food market

Abstract: 321significantly greater average tocopherol and phytosterol contents, though confectionery-type cultivars with levels of tocopherols and phytosterols similar to the best oilseed-type cultivars were identified. The large variations in kernel tocopherol and phytosterol contents found in this research suggest that there is room for breeding for increased levels of these compounds in order to develop healthier sunflower cultivars for the human food market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
4
11
0
Order By: Relevance
“…Kernel and oil phytosterol content averaged 3372 and 5268 mg kg −1 , respectively, with ranges of variation between 2954 and 3810 mg kg −1 kernel and between 4711 and 5976 mg kg −1 oil. These values are within the ranges of variation reported for sunflower germplasm (Ayerdi‐Gotor et al, 2007; Fernández‐Cuesta et al, 2012a, 2012b). However, maximum values found in the present study were considerably lower to those previously reported, particularly for oil phytosterol content for which maximum values of 7650 mg kg −1 (Ayerdi‐Gotor et al, 2007), 7251 mg kg −1 (Fernández‐Cuesta et al, 2012b), and 9752 mg kg −1 (Fernández‐Cuesta et al, 2012a) have been reported.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Kernel and oil phytosterol content averaged 3372 and 5268 mg kg −1 , respectively, with ranges of variation between 2954 and 3810 mg kg −1 kernel and between 4711 and 5976 mg kg −1 oil. These values are within the ranges of variation reported for sunflower germplasm (Ayerdi‐Gotor et al, 2007; Fernández‐Cuesta et al, 2012a, 2012b). However, maximum values found in the present study were considerably lower to those previously reported, particularly for oil phytosterol content for which maximum values of 7650 mg kg −1 (Ayerdi‐Gotor et al, 2007), 7251 mg kg −1 (Fernández‐Cuesta et al, 2012b), and 9752 mg kg −1 (Fernández‐Cuesta et al, 2012a) have been reported.…”
Section: Resultssupporting
confidence: 88%
“…Kernel phytosterol content was analyzed on two replicates per block, each of them consisting of eight randomly selected seeds. Phytosterol content was analyzed following a previously reported procedure for the analysis of free and esterified phytosterols (Fernández‐Cuesta et al, 2012a, 2012b). Gas chromatographic analysis was performed on a PerkinElmer Clarus 600 GC (PerkinElmer Inc.) equipped with a ZB‐5 capillary column (0.25 mm i.d., 30 m length, and 0.10 μm film thickness; Phenomenex).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Merah, et al (2012) reported a variation from 1523 to 2490 mg kg −1 seed (whole achene) in a population of recombinant inbred lines. Other studies based on the analysis of seed kernels have reported ranges of variation from 1426 to 4710 mg kg −1 kernel in 87 sunflower inbred lines (Fernández-Cuesta, et al, 2012a), from 2,179 to 3555 mg kg −1 kernel in 12 confectionery landraces (Fernández-Cuesta, et al, 2012b), from 2954 to 3810 mg kg −1 kernel in 22 commercial hybrids (Velasco, et al, 2013), from 1319 to 5119 mg kg −1 kernel in 985 accessions of a world collection , and from 1344.0 to 2942.5 mg kg −1 kernel in a collection of 137 Spanish landraces of confectionery sunflower .…”
Section: Variability For Seed Phytosterol Content In Sunflower Germplasmmentioning
confidence: 97%